Socioscientific Issue-Based Decision Making at Elementary School: Bibliometric Analysis - Rahayu, Galih Dani Septiyan; Maftuh, Bunyamin; Sapriya; Sopandi, Wahyu (Universitas Pendidikan Ganesha, 2024)
Decision making is a very important ability possessed by individuals at this time, especially in solving socio-scientific issues. The purpose of this study was to analyze research trends regarding socio-scientific issue-based decision making in elementary schools by conducting a bibliometric analysis of bibliographic data on technical research articles indexed by Google Scholar by combining analysis in terms of bibliometric map distribution using VOS viewer software. The research data was obtained from Google Scholar database through the Publish or Perish reference management application. The data filtering process was carried out based on the keywords